CD39 dynamics in tuberculosis: a potential biomarker of immune dysregulation and T cell exhaustion - Hao, Ling; Imran, Qari Muhammad; Ullah, Nadeem (Frontiers in Immunology, 2025)
BackgroundTuberculosis (TB), caused by Mycobacterium tuberculosis (Mtb), remains a global health crisis complicated by immune dysregulation and T cell exhaustion. CD39, an ectonucleotidase generating immunosuppressive adenosine, is implicated in cancer and chronic infections, yet its spatiotemporal role in TB pathogenesis remains unclear.MethodsMultiple publicly available datasets were utilized to evaluate CD39 across TB disease stages, diverse infectious diseases and anti-TB treatment. Diagnostic accuracy was evaluated via ROC curves and combined signature analysis. Immune cell infiltration were analyzed using CIBERSORTx. Cytokine profiles and age-stratified associations were examined. Pathway enrichment analysis was performed by GSEA. Single-cell analysis of non-human primate granulomas assessed CD39’s temporal dynamics, utilizing Monocle 3 for CD39+ T-cell trajectory analysis.ResultsCD39 was upregulated in active TB patients versus TB infection (TBI) and healthy controls (HC), correlating with older age, disease severity, and distinct expression patterns compared to other respiratory and systemic infections. CD39 demonstrated superior diagnostic accuracy over IFN-γ in distinguishing TB from TBI/HC and other respiratory diseases. Combining CD39 with TBX21 or GZMB further improved diagnostic specificity. High CD39 expression correlated with suppressed Th1 and elevated Th2/Th17/regulatory cytokines, alongside pronounced neutrophil infiltration. Age-stratified analysis revealed complex age-dependent associations of CD39 expression with various immune cell types. Single-cell analysis revealed declining CD39 transcriptional activity during prolonged infection despite expanded cellular distribution, linked to early T cell maturation followed by broader immunomodulatory shifts. Decreased CD39 expression with anti-TB treatment correlated with improved immune cell balance and resolved T cell exhaustion.ConclusionCD39 is a critical regulator of immune exhaustion and neutrophil-driven inflammation in TB, with diagnostic and therapeutic potential. Targeting CD39 may provide a novel therapeutic strategy for TB.